Linking Service Quality Dimensions to Customer Loyalty: The Mediating Influence of Customer Satisfaction in the Nepali Banking Sector - Yadav, Susmita Kumari (DAV Research Journal, 2026)
This study examines the influence of service quality dimensions on customer loyalty in the banking sector of Nepal, with particular emphasis on the mediating role of customer satisfaction. The research is based on the SERVQUAL model, which evaluates five key dimensions of service quality: tangibility, reliability, responsiveness, assurance, and empathy. A quantitative method with a descriptive and causal research design was employed to meet the study objectives. Primary data were collected from a convenience sample of 205 respondents using structured questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS). The reliability analysis indicated a high level of consistency in the results. Regression analysis showed that service quality dimensions significantly explain variations in customer loyalty. Among the five dimensions, empathy and reliability were identified the most significant predictors of customer loyalty. Furthermore, mediation analysis confirmed that customer satisfaction partially mediates the relationship between service quality and customer loyalty. The study concludes that banks in the Kathmandu Valley of Nepal could prioritize emotional engagement with customers and ensure consistent and reliable service delivery to enhance customer satisfaction and foster long-term loyalty.